Persepsi Masyarakat Terhadap Tradisi Massorong Baki Perspektif Hukum Islam - Hada, Heriya; Syatar, Abdul (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
The main problem of this research is how the views of some people in Boki Village who still carry out the Massorong tradition. This type of research is classified as qualitative with the research approach used is normative. The data sources for this research are primary and secondary data. The results show that: 1) The Massorong Baki tradition is something that has been done for a long time and is part of a group, society, usually from the same culture and religion, the most basic thing about tradition is that information is passed on from generation to generation. both verbally and in writing, they bring down offerings on the edge of the rice fields as offerings or keep the promise of the Boki people for guarding their fields until harvest. 2) The people's view of the Massorong Baki tradition is that the tool used to honor something is mandatory and as an order of courtesy and respect for those who are older or higher than us and it has been passed down from generation to generation since our ancestors. The implication of this research is that the performance of the tradition regarding this tradition also refers to the performance of the Qur'an and the sunnah of the Prophet. In addition, it is hoped that all incidents of religion related to the community will provide guidance services for community performance passively in order to avoid the subject that leads to polytheism